Achievement Motivation and Physical Fitness Levels of Soccer Athletes Representing Pidie Regency at the Aceh People’s Sports Week (PORA) - Iqbal, Muhammad (Journal Sport Academy, 2025)
This study aimed to analyze the levels of achievement motivation and physical fitness among soccer athletes representing Pidie Regency at PORA. The research employed an evaluative research design with a quantitative approach. The population consisted of all 22 soccer athletes registered for PORA, and due to the limited population size, total sampling was applied. Achievement motivation was measured using a Likert-scale questionnaire, while physical fitness was assessed through a 2.4 km running test (Cooper test). Data were analyzed using categorical scale classification and percentage analysis. The results showed that the average achievement motivation score was 131.68, categorized as moderate. Specifically, 13.63% of athletes were classified as having low motivation, 27.28% moderate motivation, and 59.09% high motivation. Meanwhile, the average physical fitness score was 11.14, which fell into the good category. The distribution indicated that 13.64% of athletes were in the low category, 50% moderate, 18.18% good, and 18.18% very good. These findings suggest that although physical fitness levels were generally good, achievement motivation still requires further enhancement to support optimal competitive performance.